Trial by CCN2: a standardized test for fibroproliferative disease? - Leask, Andrew (Springer Netherlands, 2009)
A major issue concerning clinical trials is the availability of standardized assays to evaluate drug efficacy. Ideally, such assays should test the effect of a putative drug on the expression of a biomarker in biological fluids. In a recent study by Kuiper et al. (PLOS One, 3(7): e2675). The relative levels of vascular endothelial growth factor (VEGF) and CCN2 (connective tissue growth factor [CTGF]) were examined in proliferative diabetic retinopathy (PDR). This paper is the subject of this commentary.